How is Europe responding to the plastic challenge? – An overview of strategies in selected countries - Räisänen, Milja; Mosoni, Claire; Kauppi, Sari (Finnish Environment Institute, 2022)
The global plastics challenge has evoked countries to take action to reduce the environmental and health impacts of plastics. Measures are being taken both internationally and nationally to curb the harmful impacts of plastics and to create a sustainable circular economy of plastics. The EU is steering its member states in the right direction through a number of regulatory instruments, the most recent being the SUP Directive (EU) 2019/904 on the reduction of the impact of certain plastic products on the environment, which is currently being implemented in member states. The measures and schedules for their implementation vary from country to country and include both voluntary and statutory measures. This report presents the strategies of selected European countries to address the plastics challenge. The Nordic countries (Finland, Sweden, Norway, Denmark and Iceland), the large countries (France, Germany and United Kingdom, England and Scotland in particular) and the Netherlands, a pioneer in the circular economy, are included. Information was compiled primarily from countries' plastics strategies and other administrative documents and websites during the fall and winter of 2020 and early 2021. In addition, a short survey was carried out for supplementary information in fall 2020, directed to IG Plastics working group of the EPA Network. The survey was repeated in February 2022 to obtain updated information. The amount of information found varied between countries. In addition, the use of available information was limited by the fact that some countries mainly produce information in their own language. The identified policy instruments can be categorized into regulatory, market-based, informative and financing measures, and voluntary agreements. In addition to these, the transition towards a sustainable circular economy of plastics is supported by research and development activities that build knowledge and bring changes to various stages of the plastics value chain. Substitutes for traditional plastics, such as ...